Mild, Pd-catalyzed stannylation of radioiodination targets. Issue 8 (15th April 2015) - Pickett, Julie E.; Váradi, András; Palmer, Travis C.; Grinnell, Steven G.; Schrock, Joel M.; Pasternak, Gavril W.; Karimov, Rashad R.; Majumdar, Susruta
Graphical abstract